Interaction of Mineral Nutrients and Plant Growth-Promoting Microbes for Biofortification of Different Cropping Systems - Jalal, Arshad [UNESP]; Oliveira, Carlos Eduardo da Silva [UNESP]; Gato, Isabela Martins Bueno [UNESP]; Moreira, Vitória de Almeida [UNESP]; de Lima, Bruno Horschut [UNESP]; Bastos, Andréa de Castro [UNESP]; Iqbal, Babar; Teixeira Filho, Marcelo Carvalho Minhoto [UNESP] (Springer Nature, 2024)
Micronutrient deficiency poses a significant and challenging threat to over one-third of the global population. To deal with this issue, nutrient management via biofortification is considered one of the effective and sustainable approaches. Biofortification involves multifaceted strategies such as agronomic practices—mineral and microbial interventions, conventional plant breeding, molecular and genetic engineering techniques. All these strategies fortify crops with essential elements like pro-vitamin A, vitamin C, iron, zinc, calcium, iodine, and selenium while reducing anti-nutritional factors and trypsin inhibitors in staple foods. However, most of these techniques are considered expensive and require more time than routine practices. Therefore, this review focused on the interaction among soil–plant-nutrient and their management through the introduction of plant growth-promoting bacteria, fungi, and endophytes. The aim was to enrich our understanding of how these interventions facilitate nutrient acquisition, translocation, and uptake within both plant shoots and grains. We emphasize on the use of beneficial microbes in biofortification of staple crops for sustaining human nutritional requirement. Microbes-mediated biofortification exhibits tremendous potential in enhancing the bioavailability of nutrients in staple crops, providing solution to widespread micronutrient deficiencies and nutritional security. Diversification of crop biofortification in different cropping systems is the demand of the hour to mitigate the challenges of hidden hunger. Understanding and harnessing this synergistic relationship can offer promising avenues for sustainable agriculture, addressing nutritional deficiencies, improving crop resilience, and ensuring food security in different croping systems.
Keywords: Agronomic biofortification; Malnutrition; Microbiome; Nutrients acquisition; Nutrients correction; Plants-microbes interaction; Soil dynamic